Analysis of social accounting research publications: global trends and leading contributors - Mohd Rodzi, Nor Kartini; Abdullah, Azrul (Universiti Teknologi MARA, Perlis, 2025)
Social accounting practices are being accepted worldwide due to the increasing importance of sustainability and corporate social responsibility. However, the rate of acceptance varies. Hence, this study aims to examine the major contributors, the trends, and the distribution of research documents in social accounting research to assess global research developments. This study extracted 299 publication documents from the Scopus database on 7 May 2025, covering the period from 2004 to 2024. The publication documents focus on business, management, and accounting, as research interests in this topic area are evolving. The data were analysed using bibliometric methods, with frequency analysis performed using Microsoft Excel. The results indicate that the number of publications related to "Social Accounting Research" has gradually increased over the 20-year study period since 2004. The findings reveal that the United Kingdom was the leading contributor to social accounting research. Additionally, the University of St Andrews stood out as the most prolific institution, with a total of 29 publications. Meanwhile, the most productive author is Gray, R., with 12 publications, and Bebbington, Larrinaga, and Moneva (2008) received the highest citations for their article. Accounting, Auditing & Accountability Journal was the primary source of titles related to social accounting research, with 32 publications. The keyword analysis found that "social accounting" was the most common in the documents, and the article published by Gray (2006) received the most downloads and views. These findings will assist researchers in understanding global trends and the distribution of research publications, thereby enabling them to strategise future research effectively.